Case report and review of the literature: rare fetus-in-fetu presenting as oropharyngeal epignathus - Runggaldier, Daniel; Reinehr, Michael; Friedrich, Hergen; Henze, Georg; Good, Dominic; Gysin, Claudine (Frontiers in Surgery, 2023)
An epignathus is caused by a continuous spectrum of masses of the oral cavity or oropharynx ranging in its entity from mature teratoma to the exceedingly rare fetus-in-fetu. Due to its location, regardless of the entity, the occurrence of an epignathus is frequently associated with life threatening airway obstruction. Here we demonstrate a case of a fetus-in-fetu presenting as an epignatus. We describe its successful management and review the available literature. Early diagnosis and knowledge of the preoperative workup are essential to enable a multidisciplinary management. Once the airway is secured, surgical excision is the treatment of choice often resulting in a good clinical outcome and prognosis.